Penerapan Model View Controller pada Perancangan Website Sentra Wisata Kuliner Kota Surabaya - Iqbal Ramadhani Mukhlis; Sinarring Azi Laga (Universitas Bandar Lampung (UBL), 2023)
Application of Model View Controller in Designing Surabaya Culinary Tourism Center Website - Surabaya is a city that has the potential for economic and tourism development and growth. One of the potentials being developed by the Surabaya City Government is the potential for Culinary Tourism Centers to introduce various culinary delights in the city of Surabaya. This was realized by the Surabaya City Government by establishing the Wonorejo Culinary Tourism Center (SWK) as a typical Surabaya culinary venue that has a variety of legendary culinary delights. The design of this website-based information media uses PHP 7 programming techniques and MySQL database. With the Model View Controller method and the support of the CodeIgniter framework, it aims to provide information to the public/tourists from Surabaya and outside Surabaya about various Surabaya culinary delights in the existing Culinary Tourism Centers. in Wonorejo. This study uses research methods through literature study, observation, interviews, and questionnaires. After going through internal and external testing, a value of 80.76 was obtained, which can be concluded that the information media can be used to facilitate tourists from Surabaya and outside Surabaya in obtaining information about various legendary culinary delights and other culinary delights in SWK Wonorejo.